Pemanfaatan Sekam Padi sebagai Media Tumbuh Alternatif Kegiatan Bubidaya Jamur Tiram Poktan Sangalang Hapakat - Agus Haryono; Made Dirgantara; I Nyoman Sudyana; Kalara Monica; Okta Sulistia; Yunita Silaban (Institut Pertanian Bogor, 2026)
This community engagement program aimed to enhance the capacity of the Sangalang Hapakat Farmers Group in cultivating oyster mushrooms (Pleurotus ostreatus) by utilizing rice husk as an alternative substrate to sawdust. The activities included technical training, field practice, and the supervised production of baglogs using four media formulations. Rice husk was selected due to its local abundance in Pulang Pisau’s food estate area and its high fiber content which supports mycelium growth. Results indicated that formulas with higher rice husk content (K2 and K4) accelerated mycelium colonization (25 days), pinhead formation (30–35 days), and fruit body regeneration (5–8 days). While fresh weight per baglog (1–3 ounces) showed no significant difference, mushrooms appeared whiter. Five out of nine farmers committed to continuing mushroom production using rice husk media. This innovation promotes cost efficiency, agricultural waste reduction, and production sustainability, aligning with SDGs 1, 2, 8, and 12. The program successfully transferred appropriate technology, improved farmers' skills, and presents potential for wider replication.